Mitochondrial genome diversity and evolution in Branchiopoda (Crustacea) - Luchetti, Andrea (Zoological Lett, 2019)
BACKGROUND: The crustacean class Branchiopoda includes fairy shrimps, clam shrimps, tadpole shrimps, and water fleas. Branchiopods, which are well known for their great variety of reproductive strategies, date back to the Cambrian and extant taxa can be mainly found in freshwater habitats, also including ephemeral ponds. Mitochondrial genomes of the notostracan taxa Lepidurus apus lubbocki (Italy), L. arcticus (Iceland) and Triops cancriformis (an Italian and a Spanish population) are here characterized for the first time and analyzed together with available branchiopod mitogenomes. RESULTS: Overall, branchiopod mitogenomes share the basic structure congruent with the ancestral Pancrustacea model. On the other hand, rearrangements involving tRNAs and the control region are observed among analyzed taxa. Remarkably, an unassigned region in the L. apus lubbocki mitogenome showed a chimeric structure, likely resulting from a non-homologous recombination event between the two flanking trnC and trnY genes. Notably, Anostraca and Onychocaudata mitogenomes showed increased GC content compared to both Notostraca and the common ancestor, and a significantly higher substitution rate, which does not correlate with selective pressures, as suggested by dN/dS values. CONCLUSIONS: Branchiopod mitogenomes appear rather well-conserved, although gene rearrangements have occurred. For the first time, it is reported a putative non-homologous recombination event involving a mitogenome, which produced a pseudogenic tRNA sequence. In addition, in line with data in the literature, we explain the higher substitution rate of Anostraca and Onychocaudata with the inferred GC substitution bias that occurred during their evolution. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40851-019-0131-5) contains supplementary material, which is available to authorized users.